Is split-thickness skin graft safe for coverage of the vascular pedicle in free tissue transfer?. Issue 3 (4th May 2019) - Han, Hyun Ho; Min, Kyung Hyun
Abstract: Introduction: If the pedicle is compressed after microanastomosis during free flap reconstruction, additional tissue such as skin graft or vascularized flap is needed to avoid tension. Performing a skin graft directly on the vessel might cause considerable problems. We aimed to analyze the safety of skin grafting on the anastomosis site of the free flap. Patients and methods: A total of 15 patients who underwent skin grafting on the anastomosis site were analyzed. The skin graft take-up rate and flap-related complications were evaluated postoperatively. Results: All involved sites were the extremities (10 hands and 5 feet). An anterolateral thigh free flap in six patients and a toe pulp free flap in nine patients were harvested. The mean follow-up period was 10.4 ± 6.2 months. The graft area for the pedicle was 2.8 ± 1.6 cm 2 . The percentage of final graft take was 99.3 ± 1.2% at 30 days postoperatively without flap compromise. Conclusion: During free flap surgery in the upper or lower extremities, inadequate pedicle coverage may occur easily. Applying a split-thickness skin graft in such cases can be safe and one of the simple methods.